Cardiac benign metastatic leiomyoma- a comprehensive review - Pankaj Garg; Mostafa Ali; Mohammad Alomari; J. Kenneth Schoolmeester; Mark Edgar; Carolyn K. Landolfo; Steven Attia; Kevin P. Landolfo (Cardio-Oncology)
Abstract Cardiac benign metastatic leiomyoma (BML) is a rare cardiac tumor that is usually asymptomatic, frequently misdiagnosed and may result in serious complications, including embolization, heart failure and death. This review highlights the importance of considering cardiac BML in the differential diagnosis of cardiac masses, especially in women with a history of uterine leiomyomas. This review summarizes the current knowledge about cardiac BML, including its demographics, clinical presentation, etio-pathogenesis, diagnosis, and management. The authors discuss the challenges associated with diagnosing cardiac BML and emphasize the importance of a thorough history, physical examination, and imaging studies. They also review the different treatment options for cardiac BML, including surgical resection and role of medical and surgical castration. Early diagnosis and management of cardiac BML is crucial to prevent complications. This review provides valuable insights for clinicians who may encounter this rare condition. By raising awareness of cardiac BML and its management strategies, this review can improve patient care and outcomes.